Synchrotron XPS and Electrochemical Study of Aging Effect on Passive Film of Ni Alloys. Issue 2 (16th February 2023) - Eidhagen, Josefin; Larsson, Alfred; Preobrajenski, Alexei; Delblanc, Anna; Lundgren, Edvin; Pan, Jinshan
Abstract : To investigate aging effect on the passive film of Ni23Cr15Mo and Ni22Cr9Mo3Nb, synchrotron-based X-ray photoelectron spectroscopy (XPS) was used to analyze the structure and composition of the air-formed passive film on the alloys. The corrosion resistance of the two Ni alloys in 1 M NaCl solution was evaluated with electrochemical cyclic polarization measurement. The synchrotron XPS measurement provided detailed information about chemical states of alloying elements in the passive film, showing that the passive film consists of an inner oxide layer and an outer hydroxide layer. The XPS data allowed precise determination of the chemical composition and the thickness of the outer hydroxide layer, the inner oxide layer, and the underlying subsurface alloy layer. The Cr-oxide in the inner layer grows thicker with aging time, leading to Cr-depletion in the subsurface region. Mo and Nb in the alloy form mixed oxides and hydroxides, and aging in air leads to transformation of the lower valence oxides into higher valence oxides. The freshly formed oxide film exhibits similar barrier properties as the aged oxide film. The stability of the passive film formed on Ni22Cr9Mo3Nb seems to be better than that on Ni23Cr15Mo.